Evolution of anodic erosion components and heat transfer efficiency for W and W80Ag20 in atmospheric-pressure arcs. (2nd September 2020) - Cui, Yufei; Wu, Yi; Niu, Chunping; Rong, Mingzhe; Sun, Hao; Niu, Lizhuang; Xiong, Qiancun; Liu, Weiwei
Abstract: Based on the in situ diagnostic system and the digital image post-processing technique, quantifications of the anodic erosion components and heat transfer efficiency for tungsten and the W80 Ag20 material in arcs of argon, helium, and nitrogen were achieved. The leading vaporization of silver has been found to result in evidently lower anodic heat transfer efficiency and much smaller molten pools compared with those of the tungsten anode, but the intensive generation of silver vapor under the melt layer causes higher splashing erosion of the W80 Ag20 anode. However, these characteristics can be strongly changed by the cathodic blowing, which leads to a much higher splashing erosion of tungsten anode but a lower erosion rate of W80 Ag20 anode. Through the visualization of the erosion behavior and the post microanalysis of the anode surface, the possible driving mechanisms for the generation of the splashing droplet were discussed. The result indicates that the local high pressure caused by the vapor blasting during the bubble explosion plays a key role in the detachment of splashing droplets. Furthermore, as for the tungsten-based anode, the comparison of erosion behavior between the W80 Ag20 anode and the previous-studied W70 Cu30 anode makes it clear that increasing the temperature difference between the melting point (MP) of tungsten and the boiling point (BP) of the other material has the pros and cons. It is effective for the decrease of the anode erosion when the anode heat energy is relatively weak, while it can promote the splashing erosion when the liquid tungsten layer has been formed on the anode tip. These results are beneficial for the optimal design of the electrode system in circuit breakers.